Investigating the non-protein binding targets of the Teneurin extracellular domain and their biological significance - Crowther, O (2022)
The adhesion protein teneurin is known to control brain development and neuronal migration. Much of the research centered around teneurin thus far has probed its protein binding partners, of which the aGPCR Lphn, and FLRT protein are most extensively studied. One as yet understudied binding partner of the teneurin extracellular domain are the glycosaminoglycan (GAG) macromolecules abundant in the brain extracellular matrix (ECM). These highly charged glycans are made up of five main families: Heparin/ Heparan sulfate (HS); Chondroitin sulfate (CS); Dermatan sulfate; Keratan sulfate; and Hyaluronic acid. These glycans, specifically HS and CS species, have been shown to be important modulators of neuronal migration, as well as factors dictating CNS plasticity and trauma recovery. The work in this thesis proves that binding of HS and CS ligands occurs on a highly charged patch on the large YD-shell scaffold which forms the majority of the teneurin ecto-domain. Two crystal structures were solved here with glycan ligands, proving the binding site contacts 6 Arginine and Lysine residues on the teneurin surface. Subsequent mutation of this binding site abolished binding, and was confirmed by pulldown assay. In vitro cell based migration assays began to unearth the effects of glycan binding of HEK and N2A cell migration, with a view to the effect of glycan binding in the developing brain. This work illustrates the first time teneurin–glycan complexes have been investigated structurally, and represents an introduction into the study of glycobiology with respect to teneurin and how this may control neuronal development.